The Triangle Man and the flightless diwata - Osias, Kate; Fernandez, Dex; Garlitos, Rhandee (Quezon City : CANVAS, 2015)
"A man with a triangle for a head and a diwata that cannot fly suffer the endless teasing and taunting of mean fairies. What will happen when the two outcasts meet?"--Cover
Winner, CANVAS' Romeo Forbes Children's Storywriting Competition
Keywords: Children's stories, Filipino; Electronic Books